2016
DOI: 10.1534/genetics.116.187286
|View full text |Cite
|
Sign up to set email alerts
|

Mitonuclear Epistasis for Development Time and Its Modification by Diet in Drosophila

Abstract: Mitochondrial (mtDNA) and nuclear genes have to operate in a coordinated manner to maintain organismal function, and the regulation of this homeostasis presents a substantial source of potential epistatic (G × G) interactions. How these interactions shape the fitness landscape is poorly understood. Here we developed a novel mitonuclear epistasis model, using selected strains of the Drosophila Genetic Reference Panel (DGRP) and mitochondrial genomes from within Drosophila melanogaster and D. simulans to test th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
167
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(176 citation statements)
references
References 105 publications
(136 reference statements)
8
167
1
Order By: Relevance
“…; Mossman et al . ). The presence of such ‘G × G × E interactions’ indicates that the effects of disrupting coadapted mitonuclear genotypes may vary across environments.…”
Section: Mitonuclear Incompatibilities and Species Boundariesmentioning
confidence: 99%
See 1 more Smart Citation
“…; Mossman et al . ). The presence of such ‘G × G × E interactions’ indicates that the effects of disrupting coadapted mitonuclear genotypes may vary across environments.…”
Section: Mitonuclear Incompatibilities and Species Boundariesmentioning
confidence: 99%
“…; Mossman et al . ). These efforts have shown extensive mitonuclear epistasis for many fitness‐related measures that can exhibit diverse interaction patterns (Fig.…”
Section: Mitonuclear Incompatibilities and Species Boundariesmentioning
confidence: 99%
“…Indeed, interactions between organellar genomes (mitochondria and plastids) and host genotypes appear to often affect host fitness (e.g., refs. [17][18][19][20].…”
mentioning
confidence: 99%
“…A recent report has also indicated that rapamycin can inhibit the inflammatory reaction induced by nuclear factor (NF)-κB activation and neutrophils (2,3). Rapamycin also reportedly exacerbates the severity of acute lung injury induced by endotoxin and causes cell apoptosis (4).…”
Section: Introductionmentioning
confidence: 99%